Economic impact of contact force sensing in catheter ablation for atrial fibrillation. (3rd October 2019) - Mansour, Moussa; Reddy, Vivek Y.; Karst, Edward; Heist, Edwin Kevin; Packer, Douglas L.; Dalal, Nirav; Agarwal, Rahul; Calkins, Hugh; Ruskin, Jeremy N.; Mahapatra, Srijoy
Abstract: Aims: The TactiCath Contact Force Ablation Catheter Study for Atrial Fibrillation (TOCCASTAR) clinical trial compared clinical outcomes using a contact force (CF) sensing ablation catheter (TactiCath) with a catheter that lacked CF measurement. This analysis links recorded events in the TOCCASTAR study and a large claims database, IBM MarketScan®, to determine the economic impact of using CF sensing during atrial fibrillation (AF) ablation. Methods and Results: Clinical events including repeat ablation, use of antiarrhythmic drugs, hospitalization, perforation, pericarditis, pneumothorax, pulmonary edema, pulmonary vein stenosis, tamponade, and vascular access complications were adjudicated in the year after ablation. CF was characterized as optimal if greater than or equal to 90% lesion was performed with greater than or equal to 10 g of CF. A probabilistic 1:1 linkage was created for subjects in MarketScan® with the same events in the year after ablation, and the cost was evaluated over 10 000 iterations. Of the 279 subjects in TOCCASTAR, 145 were ablated using CF (57% with optimal CF), and 134 were ablated without CF. In the MarketScan® cohort, 9811 subjects who underwent AF ablation were used to determine events and costs. For subjects ablated with optimal CF, total cost was $19 271 ± 3705 in the year after ablation. For ablation lacking CF measurement, cost was $22 673 ± 3079 (difference of $3402, P  < .001). In 73% of simulations, optimal CF was associated with lower cost in the year after ablation. Conclusion: Compared to ablation without CF, there was a decrease in healthcare cost of $3402 per subject in the first year after the procedure when optimal CF was used.